Intellectuals and Japanese Buddhism in Brazil - de Albuquerque, Eduardo Basto [UNESP] (Nanzan Inst Religion Culture, 2008)
This study concentrates on the discovery of Japanese Buddhism by Brazilian intellectuals as a group of spiritual practices and as a body of spiritual wisdom. The study has been realized through readings and meetings with Japanese Buddhist monks and/or Japanese immigrants. These intellectuals defend a religious experience based on a universal notion of representations of Japanese Buddhism, which provides them with a non-dualistic philosophical perspective and a unique psychological experience. Through innovative spiritual experiences these intellectuals have broken the tension created within the dispute between secularized science and the Catholic hegemony, both predominant in the intellectual panorama.
Keywords: Japanese Buddhism; intellectuals; Zen in Brazil; Buddhism in Brazil